Pectin-Coated Plasmonic Nanoparticles for Photodynamic Therapy: Inspecting the Role of Serum Proteins - Cisneros, José Sebastián (2021)
Plasmonic metal nanoparticles (NPs) can be used as enhancers of the efficiency of standard photosensitizers (PSs) in photodynamic therapy (PDT). Protein corona, the adsorption layer that forms spontaneously around NPs once in contact with biological fluids, determines to a great extent the efficiency of PDT. In this work, we explore the possibility that pectin-coated Au NPs (Au@Pec NPs) could act as adjuvants in riboflavin (Rf)-based PDT by comparing the photodamage in HeLa cells cultured in the presence and in the absence of the NPs. Moreover, we investigate the impact that the preincubation of Rf and Au@Pec NPs (or Ag@Pec NPs) at two very different serum concentrations could have on cell's photodamage. Because reactive oxygen species (ROS) precursors are the excited states of the PS, the effect of proteins on the photophysics of Rf and Rf/plasmonic NPs was studied by transient absorption experiments. The beneficial effect of Au@Pec NPs in Rf-based PDT on HeLa cells cultured under standard serum conditions was demonstrated for the first time. However, the preincubation of Rf and Au@Pec NPs (or Ag@Pec NPs) with serum has undesirable results regarding the enhancement of Rf-based PDT. In this sense, we also verified that more concentrated protein conditions result in lower amounts of the triplet excited state of Rf and thus an expected lower production of ROS, which are the key elements for PDT's efficacy. These findings point out the relevance of serum concentration in the design of in vitro cell culture experiments carried out to determine the best way to combine and use potential sensitizers with plasmonic NPs to develop more effective PDTs.